Climate crisis - Vrečko Ilc, Blaž (Teorija in praksa, 2021)
The purpose of the article is to open up epistemological space for revitalising the idea of democratic economic planning as a viable alternative vision. It argues that a proper development of the idea must be preceded by a comprehensive critical interrogation of a hegemonic multidimensional ideological mystification of capitalism and its markets. By utilizing Marxist and eco-socialist insights the article identifies and analyses several central ideological mystifications that enact an epistemic closure. These range from the obfuscation of capitalism's role in creating the climate crisis as an inherently unsustainable system, to the mystification of its non-evolutionary origins, to the obfuscation of the role economic planning plays in contemporary capitalism, to the mystification of markets as ideal spaces of freedom and innovation obfuscating the ever present market-related oppression, exploitation and environmental devastation, and to silencing concrete historical examples of democratic economic planning such as project Cybersyn that should serve as an inspiration for imagining an alternative order
Keywords: capitalism; climate change; democratic economic planning; demokratično ekonomsko načrtovanje; Ecological crisis; Ekološka kriza; ideological mystification; ideološka mistifikacija; kapitalizem; klimatske spremembe; Neoliberalism; Neoliberalizem